Photography's Second Front: Kodak's Serving Human Progress Through Photography Institutional Advertising Campaign. (2nd April 2016) - Snow, Rachel
Abstract : This paper examines Kodak's 'Serving Human Progress through Photography' campaign, which ran in the United States during World War I and World War II and emphasized themes of US nationalism and progress through technology. While Kodak's peacetime consumer advertisements were ultimately designed to sell photographic goods and products, this institutional advertising campaign sought to build brand recognition, consumer loyalty, and a positive corporate image by humanizing the private corporation and portraying it as a public servant. Therefore, these advertisements sought to legitimize not only Kodak, but the idea of the corporation as an indispensible public institution, allied with the US government in times of war and crisis. War, though presenting some important challenges to Kodak, proved an opportune time to harness the expertise of the advertising industry to cement long-term relationships with the American public and to secure the most valuable outcome of all, loyalty to the idea of a corporatized photographic culture. The versatility of the photographic medium and its uses in a diverse array of contexts easily lent itself to the campaign's arguments about Kodak's indispensability to the progress of humanity. This article explains how in times of war, Kodak shrewdly attended not only to selling goods and services, but also to selling itself as an American institution, a corporation in the service of nation.